2009
DOI: 10.1097/meg.0b013e32830b8acf
|View full text |Cite
|
Sign up to set email alerts
|

Screening colonoscopy for colorectal cancer prevention: results from a German online registry on 269 000 cases

Abstract: Colonic neoplasias are detected in about 20% of patients most of which are immediately removed by polypectomy at a low risk. Polypectomy of adenomas and low UICC stages in cancer patients during screening colonoscopy may be tools for fighting colorectal cancer mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
3
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 31 publications
2
42
3
4
Order By: Relevance
“…The differences in adenoma prevalence between these studies were substantial (and varied between 0.14 [27] and 0.33 [28] at age 55 for example). Some Asian studies reported relatively high adenoma prevalence [28][29][30], and a German study relatively low [31]. This is the opposite of what one would expect based on the CRC incidence in these countries.…”
Section: Discussionmentioning
confidence: 91%
“…The differences in adenoma prevalence between these studies were substantial (and varied between 0.14 [27] and 0.33 [28] at age 55 for example). Some Asian studies reported relatively high adenoma prevalence [28][29][30], and a German study relatively low [31]. This is the opposite of what one would expect based on the CRC incidence in these countries.…”
Section: Discussionmentioning
confidence: 91%
“…A recent meta-analysis involving 68 324 participants showed that the yield of advanced colonic neoplasia from colonoscopic screening of a heterogeneous population of high-and average-risk asymptomatic individuals was 5·8 per cent, with invasive cancers accounting for 0·8 per cent 14 . Analysis of a further 269 144 screening colonoscopies performed on a similar population of asymptomatic patients demonstrated the yield of advanced colonic neoplasia and colorectal cancer to be 7·9 and 0·8 per cent respectively 15 . In the present study, patients with a radiological diagnosis of acute uncomplicated diverticulitis had a prevalence of advanced colonic neoplasia and colorectal cancer similar to, or less than that of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…However, these recommendations were systematically based on comparison with published general population risks of colon carcinoma from registries of screening colonoscopies, which were estimated to be between 0.8 and 1 % [24,25], and not with the adjusted risk in the local reference populations. In addition, the conditional exemption mentioned by some authors, based on certain criteria, such as the absence of warning signs of colon carcinoma, disregards the fact that the supposed predictors of cancer were not assessed in a diverticulitis population.…”
mentioning
confidence: 99%